Multicultural Education Based on Hindu Philosophy and the Internalization of the Value of Religious Moderation in Pasraman Saraswati Tri Parartha Mataram - Andari, Ida Ayu Made Yuni; Wiguna, Ida Bagus Alit Arta; Candrawati, Desak Made; Endrawan, I Made Tama (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2025)
Pasraman Saraswati Tri Parartha Mataram integrates multicultural education grounded in Hindu philosophy to instill the value of religious moderation. This research departs from the discourse of religious education, which not only focuses on theological aspects but also on the formation of inclusive, contextual, and moderate social character and religious ethics. The purpose of this study is to identify the learning strategies used by Acarya in teaching the values of religious moderation and analyze their contribution to the social attitudes and religiosity of pasraman students. This study employs a qualitative case study approach, focusing on the main subjects: Acarya, Sisya, and parents. We collected data through in-depth interviews, participatory observations, and documentation, followed by a thematic analysis. The findings of the study show that the internalization of the value of religious moderation runs effectively through learning approaches rooted in Hindu philosophy, such as Tat Twam Asi, Ahimsa, and Vasudhaiva Kutumbakam. Learning strategies that combine ritual practices, examples, and strengthening social attitudes have been proven to be able to form a character that is tolerant, religious, and respectful of differences. The main contribution of this article lies in offering a contextual model of local religion-based multicultural education that can be replicated in other religious educational institutions. The results of this study are important for the development of religious education, educational philosophy, and da'wah communication based on local culture and spirituality as a transformative approach to strengthening religious moderation in pluralistic societies.